Kvantitativna raščlamba članaka objavljenih u Vjesniku bibliotekara Hrvatske - Bačić, Mira (Array, 2007)
The research goal was to get numerical indicators about scientific and professional articles published in the journal Vjesnik bibliotekara Hrvatske during the period of forty nine years. The total of 605 scientific and professional articles were published. They were arranged in ten year periods and fourteen thematic units. The biggest number of articles (137) was published from 1991 to 2000. Equal number of articles was distributed within the following thematic units: bibliography, funds/collection development, cataloguing, classification, users, and librarian education. Most of the articles are classified under the thematic unit library management (189). If the disposition of thematic units is observed according to a library type, the majority of articles are not about any particular type of library (363). Most of the remaining 242 articles are about public libraries (76), and only nine are about school libraries. 187 articles were categorized for the period since 1998. Of these, professional articles make up the largest part (36%), followed by review articles (20%), and scientific articles (16%). The total number of authorships was 704, which equals 1.16 authors per article. Women authors are in majority (70% of total number of articles). 244 authors published only one article in VBH, and only one author published 14 articles. Foreign authors make up 8% of the author structure (59 articles) and the biggest number of foreign authors was published in the fifth decade (28). The research has confirmed the thematic variety of articles published in VBH, but not the equal coverage of all types of libraries in Vjesnik bibliotekara Hrvatske